Biochemically induced phosphate precipitation in enhanced biological phosphorus removal system: Mechanism, application and future directions - Shipeng Li; Xiaoli Zhou; Xuandi Cao; Ruochen Wang; Zheqin Dai; Haq Nawaz Abbasi; Guangcan Zhu; Hongya Geng; Xingang Wang; Hongliang Dai (Water Research, 2026)

Correction to: Genome-wide identification unravels the role of the arabinogalactan peptide (AGP) gene family in cotton plant architecture - Junfeng Tang; Teame Gereziher Mehari; Dongmei Qian; Ruochen Li; Zhengyang Chen; Zitong Zhou; Yuchun Yan; Haodong Chen; Wei Wang; Baohua Wang (Plant Cell Reports, 2026)

Study on the Effect of Elevators in the Vertical Plane on the Motion Performance of a Twin Hybrid Autonomous Underwater Vehicle by Simulation - Jiafeng Huang; Kele Zhou; Hyeung-Sik Choi; Ruochen Zhang; Phan Huy Nam Anh; Dong-Wook Jung; Mai The Vu (Journal of Marine Science and Engineering, 2025)
The Twin Hybrid Autonomous Underwater Vehicle (THAUV) is an underwater monitoring system consisting of a twin buoyant body and a fixed wing mounted between them. It is equipped with two propeller thrusters and a pair of elevators at the aft end. As a new type of underwater vehicle, it combines the long endurance of an underwater glider (UG), the high-speed maneuverability of an autonomous underwater vehicle (AUV), and the ability to carry larger payloads. In this paper, the motion equations of the THAUV are established, and its simulation model is developed using SIMULINK. Computational fluid dynamics (CFD) is further employed to identify hydrodynamic parameters under different elevator size conditions. A case study is conducted to analyze the effects of three different widths of elevators on glide performance, including gliding speed, pitching angle, and gliding trajectory. CFD results show that when the elevator deflection angle is zero, the hydrodynamic forces acting on the THAUV increase as the elevator width increases under identical angle of attack and velocity conditions. Under CFD conditions with fixed angle of attack and flow velocity, the sensitivity of the hydrodynamic characteristics to elevator deflection became significantly more pronounced. Increasing the elevator deflection angle led to substantial growth in the generated hydrodynamic forces. Motion simulations further show that increasing the elevator deflection angle enhances the THAUV’s gliding performance. Comparative results also reveal that glide performance improves with larger elevator width.

Evaluation of the degree of blending between virgin and aged asphalt in rejuvenated asphalt mixture based on multilayer inclusion theory - Jinguo Ge; Huanan Yu; Guoping Qian; Taojun Li; Yixiong Zhong; Ruochen Lei; Liang Zhou; Yuetan Ma; Tengfei Nian (Journal of Cleaner Production, 2025)

Intrinsic ion migration-induced susceptible two-dimensional phase-transition memristor with ultralow power consumption - Lanhao Qin; Yimeng Yu; Cheng Fang; Yujie Liu; Kaichen Zhu; Decai Ouyang; Shenghong Liu; Bailing Song; Ruochen Zhou; Mario Lanza; Wenhua Hu; Jinsong Wu; et al. (Science Bulletin, 2025)

Genome-wide identification unravels the role of the arabinogalactan peptide (AGP) gene family in cotton plant architecture - Junfeng Tang; Teame Gereziher Mehari; Dongmei Qian; Ruochen Li; Zhengyang Chen; Zitong Zhou; Yuchun Yan; Haodong Chen; Wei Wang; Baohua Wang (Plant Cell Reports, 2025)

Bottom-up nucleation induced conformal crystallization for inverted MA-free perovskite solar cells on textured substrates - Ruochen Liu; Jiawei Xu; Tianxiang Hu; Xiang Li; Kongxiang Wang; Qi Huang; Zhongtao Duan; Hong Liu; Weifan Qian; Haiting Zhou; Chunxiao Cong; Xiaofei Yue; et al. (Chemical Engineering Journal, 2025)

Removal of 48 per- and polyfluoroalkyl substances (PFAS) throughout processes in domestic and general industrial wastewater treatment plants: Implications for emerging alternatives risk control - Yueqing Zhang; Ruochen Dong; Feng Ge; Minghui Hong; Zhanghao Chen; Yunqiao Zhou; Jing Wei; Cheng Gu; Deyang Kong (Journal of Hazardous Materials, 2024)

AtHD2D is involved in regulating lateral root development and participates in abiotic stress response in Arabidopsis - Yueyang Chu; Ruochen Duan; Haoran Song; Wenshuo Zhang; Yuxuan Zhou; Yutong Ma; Xiaotong Yin; Lining Tian; Israel Ausin; Zhaofen Han (Journal of Plant Physiology, 2024)

Emerging and legacy per- and polyfluoroalkyl substances (PFAS) in fluorochemical wastewater along full-scale treatment processes: Source, fate, and ecological risk - Yueqing Zhang; Yunqiao Zhou; Ruochen Dong; Ninghui Song; Minghui Hong; Juying Li; Jia Yu; Deyang Kong (Journal of Hazardous Materials, 2024)

Effect of high-fat diet on cerebral pathological changes of cerebral small vessel disease in SHR/SP rats - Yuchi Zhang; Abdullah Md. Sheikh; Shatera Tabassum; Kenichi Iwasa; Abu Zaffar Shibly; Xiaojing Zhou; Ruochen Wang; Jubo Bhuiya; Fatema Binte Abdullah; Shozo Yano; Yoshihito Aoki; Atsushi Nagai (GeroScience, 2024)

One-step processing of waste dredged slurry into planting soil by targeted pretreatment and vacuum filtration - Silin Wu; Xiao Peng; Xiaohui Sun; Zijun Dong; Aizhao Zhou; Lei Zhang; Ruochen Wang (Journal of Environmental Management, 2024)

Genetic and pathogenic characterization of an NADC-34-like isolate of porcine reproductive and respiratory syndrome virus - Yongxin Zhao; Ruiqing Wang; Wei Li; Chenfei Yu; Riteng Zhang; Ruochen Hu; Ruhai Guo; Zengqi Yang; Yefei Zhou; Xinglong Wang (Archives of Virology, 2023)

AI-powered automatic detection of dynamic triggering of earthquake based on microseismic monitoring - Fengrun Jiang; Feng Dai; Jingren Zhou; Ruochen Jiang (Soil Dynamics and Earthquake Engineering, 2023)

How magnitude of PM2.5 exposure disparities have evolved across Chinese urban-rural population during 2010–2019 - Ming Liu; Yang Wang; Ruochen Liu; Chao Ding; Gaoxiang Zhou; Ling Han (Journal of Cleaner Production, 2023)